Assessing the prerequisites for integrating artificial intelligence in secondary education: Perspectives of teachers in Saudi Arabia - Alkhuzaim, Khalid Mohammed; Alzuhair, Nouf Fahad; Al-Qutaim, Asmaa Muhammad (Journal of Asian Scientific Research, 2024)
This study investigates the essential prerequisites for the effective integration of artificial intelligence (AI) into secondary education in the Kingdom of Saudi Arabia, assessing the perceptions of both male and female educators. Employing a descriptive survey methodology, the primary data collection tool consists of questionnaires administered to 427 secondary school teachers in Riyadh. The findings reveal a notable average agreement level (mean score of 4.43) among participants concerning the identified prerequisites for implementing AI. Notably, students’ requirements scored the highest (average of 4.51), followed closely by those for teachers (average of 4.48), the educational environment (average of 4.46), and educational content (average of 4.25). Each category demonstrates consistently high importance. Gender-based analysis indicates no statistically significant difference in determining prerequisites, except for those expected from teachers and the educational environment, which garnered preference from female educators. Similarly, no statistically significant variance emerged in the identification of prerequisites based on major. Regarding teaching experience, no statistically significant difference was found in determining prerequisites, except for requirements related to the educational environment, where educators with 10-15 years of experience exhibited a preference. The study concludes that qualification does not significantly impact the determination of prerequisites for AI in secondary education. This study offers useful insights into the perspectives and requirements of educators, providing detailed knowledge of the integration of artificial intelligence (AI) into secondary education in Saudi Arabia. It highlights important factors that need to be considered for the effective deployment of AI in education.